2017
DOI: 10.1186/s12983-017-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Muscle development in the shark Scyliorhinus canicula: implications for the evolution of the gnathostome head and paired appendage musculature

Abstract: BackgroundThe origin of jawed vertebrates was marked by profound reconfigurations of the skeleton and muscles of the head and by the acquisition of two sets of paired appendages. Extant cartilaginous fish retained numerous plesiomorphic characters of jawed vertebrates, which include several aspects of their musculature. Therefore, myogenic studies on sharks are essential in yielding clues on the developmental processes involved in the origin of the muscular anatomy.ResultsHere we provide a detailed description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 80 publications
4
43
0
Order By: Relevance
“…In most amphibians investigated by Ziermann (), the mandibular and hyoid arch muscles develop more or less simultaneously, with a delay in the development of the branchial arch muscles. The hypobranchial muscles also usually develop later than the mandibular and hyoid arch muscles in N. forsteri and amphibians (present study; Ericsson et al, ; Ziermann, ), as well as in the small‐spotted catshark Scyliorhinus canicula (Ziermann et al, ) and the Senegal bichir Polypterus senegalus (Noda et al, ), with what we assume to be the ancestral condition for gnathostomes.…”
Section: Ontogeny/phylogenysupporting
confidence: 70%
“…In most amphibians investigated by Ziermann (), the mandibular and hyoid arch muscles develop more or less simultaneously, with a delay in the development of the branchial arch muscles. The hypobranchial muscles also usually develop later than the mandibular and hyoid arch muscles in N. forsteri and amphibians (present study; Ericsson et al, ; Ziermann, ), as well as in the small‐spotted catshark Scyliorhinus canicula (Ziermann et al, ) and the Senegal bichir Polypterus senegalus (Noda et al, ), with what we assume to be the ancestral condition for gnathostomes.…”
Section: Ontogeny/phylogenysupporting
confidence: 70%
“…) that is often erroneously described as an appendicular muscle in fishes (see e.g., Diogo & Ziermann, ; Ziermann et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…(, 2016), Diogo & Ziermann (), Miyashita & Diogo (), and Ziermann et al. (). The latter authors reviewed comparative, paleontological, and developmental data and suggested that the pectoral‐pelvic musculature similarity seen in teleosts is a derived, homoplastic feature acquired independently in the evolutionary transition leading to these fishes, somewhat mirroring the homoplastic similarity seen in other derived gnathostome groups, such as tetrapods.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations